Programme for Oireachtas festival, 1963 (in Irish) - Gaelic League Choir, London, GLCL
Irish-language Programme for a series of events to take place at Oireachtas, Dublin, from 17 to 27 Deireadh Fómhair (October) 1963. Includes adverts for Dublin businesses.